2022
DOI: 10.1038/s41467-022-29513-z
|View full text |Cite
|
Sign up to set email alerts
|

Course of post COVID-19 disease symptoms over time in the ComPaRe long COVID prospective e-cohort

Abstract: About 10% of people infected by severe acute respiratory syndrome coronavirus 2 experience post COVID-19 disease. We analysed data from 968 adult patients (5350 person-months) with a confirmed infection enroled in the ComPaRe long COVID cohort, a disease prevalent prospective e-cohort of such patients in France. Day-by-day prevalence of post COVID-19 symptoms was determined from patients’ responses to the Long COVID Symptom Tool, a validated self-reported questionnaire assessing 53 symptoms. Among patients sym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 24 publications
16
154
1
8
Order By: Relevance
“…Risk factors for the chronification of symptoms may include having several symptoms at time of testing and the presence of cognitive symptoms evidenced by a difficulty concentrating. A recent study described the longitudinal evolution of symptoms over 12 months and suggested neurologic symptoms such as paresthesia might increase with time 16 . This is in line with our hypothesis that the chronification of symptoms may be driven by a neurological process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for the chronification of symptoms may include having several symptoms at time of testing and the presence of cognitive symptoms evidenced by a difficulty concentrating. A recent study described the longitudinal evolution of symptoms over 12 months and suggested neurologic symptoms such as paresthesia might increase with time 16 . This is in line with our hypothesis that the chronification of symptoms may be driven by a neurological process.…”
Section: Discussionmentioning
confidence: 99%
“…Without current treatment options, and as more evidence is gathered to explain the underlying pathophysiology, time and the natural evolution of symptoms accompanied by interdisciplinary care, rehabilitation and the management of daily activities remain the cornerstone of therapy 11 13 . While the prevalence of persistent symptoms decreases with time 5 , 14 16 , a subset of patients develop chronic symptoms that may impact them on the long-term. Thus, infected individuals could potentially be categorized into three groups: acute infection without post-COVID condition, acute infection with post-COVID condition, and acute infection with post-COVID condition and a chronification of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in this case, the impact can be substantial particularly in the social aspect of life. As suggested in 6-month or longer prospective follow-up studies of post-COVID patients [ 15 16 17 ], physical symptoms including anosmia, chest tightness, or cough may improve over time, but psychological and social issues may persist for longer periods of time. Job loss is another frequent complication [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, brain analyses were also performed across these studies using different methodological strategies, especially related to the aforementioned activity normalization methods. Finally, the time from symptom onset is certainly the major factor interfering with symptoms and PET results, considering possible brain recovery [ 23 ]. All these points are in favour of future larger multicentre studies with harmonized and standardized protocols for inclusion, data acquisition, and image processing.…”
Section: Brain Fdg Pet Imaging Of Patients With Long Covid In the Lit...mentioning
confidence: 99%